Literasi Manajemen dalam Pengembangan Usaha Pengelolaan Desa Wisata di Way Tebing Cepa, Kabupaten Lampung Selatan - Indriyani, Susi; Sari, Pipit Novila; Nurhartanto, Adhi; Hairudin, Hairudin (ANDASIH Jurnal Pengabdian kepada Masyarakat, 2025)
Improving management literacy among tourism village managers is important in supporting the sustainability and optimization of village tourism potential. This article discusses the results of community service activities aimed at improving management literacy in tourism awareness groups (Pokdarwis) in Way Tebing Cepa, South Lampung Regency. This activity involved 30 participants and was carried out on November 28, 2024 in Taman Baru Village, Kalianda, which was opened by the Head of Taman Baru Village. Before the training, the average level of understanding of participants in management literacy was 50. After the training, there was an increase in understanding with an average value reaching 75. With better management literacy, managers are expected to be able to develop tourism villages more professionally and sustainably. This article also presents a discussion on the impact of management literacy on the sustainability of tourism villages based on relevant literature..